Connected riparian reserves retain high avian phylogenetic diversity in Amazonian oil palm. (July 2021) - Cardoso, Maira R.; Matos, Fabio A.R.; Almeida, Sara M.; Silva, Larissa C.; Cerqueira, Pablo V.; Santos, Marcos P.D.; Edwards, David P.
Abstract: Expansion of oil palm is a major driver of deforestation and species losses. Retention of forested riparian reserves within agricultural landscapes helps to minimize the negative effects on biodiversity and offers refuges for forest species. A key unknown is the evolutionary range and diversity of species that these reserves can support, and which elements of landscape configuration enhance the conservation of phylogenetic diversity. We focus on birds in the Eastern Amazon, a region with rapid expansion of oil palm. Using point counts, we sampled in eleven transects per habitat type: large forest fragments (the most intact forests in the region); riparian reserves, and oil palm plantation. Riparian reserves spanned a variety of widths, distances to nearest forest patches, and connectivity with fragments. Riparian reserves support similar phylogenetic diversity and distinctiveness to large forest fragments and on average 200 million more years of evolutionary history than oil palm plantations. Evolutionary Distinctiveness (ED) was directly impacted by landscape configuration, with lower ED in riparian reserves connected to forest, while Phylogenetic Diversity (PD) and the Mean Pairwise Distance (MPD) in connected riparian reserves and closer to forest was slightly higher. In finding that riparian reserves retain significant avian phylogenetic diversity and distinctiveness, we underscore their key role in maintaining landscape-level biodiversity within oil palm and provide evidence for their continued protection. Support for the importance of maintaining connectivity to forest fragments in protecting phylogenetic diversity suggests that conservation actions should ensure that riparian zones remain connected, potentially benefiting biodiversity within otherwise-isolated forest fragments that dominate the Eastern Amazon.